Modelling of the relationship between sustainability and shareholder wealth - Pavláková Dočekalová, Marie; Kocmanová, Alena; Meluzín, Tomáš; Škapa, Stanislav (Technological and Economic Development of Economy, 2022)
A structural model for the verification of the causal relationship between sustainability and economic value added is presented in this paper. The study has shown that there is no definite and unique relationship between corporate sustainability and economic value. Based on the results of the structural modelling, sustainable value model ESGVA is methodologically improved. The model expresses all four dimensions of corporate sustainability: environmental, social, corporate governance and economic. The case study demonstrates how different the results are if a purely economic concept of company value is used compared to value that takes into account environmental, social and corporate governance factors. The model is applicable to comparative analysis of socially responsible investments. Sustainable value provides extra information on corporate performance and can be used for decision-making of individual investors.First published online 17 March 2022